Implikasi Penggunaan Alat Sadap “Zero-Click ” Dalam Penanganan Kasus Cyber Crime - Dewa Gede Ary Krisna; Ida Ayu Putu Widiati; Ni Made Sukaryati Karma (Fakultas Hukum Universitas Warmadewa, 2025)
In Indonesia, technological progress is very rapid, but some people take advantage of this by committing criminal acts. This will have an impact on the protection of personal data. CyberCyber security in the form of wiretapping has a very important role. The formulation of the problem raised is 1) how is the regulation of the use of